The Effect of Family Structure on Female Labor Participation – Empirical Analysis based on the 2011 China Health and Retirement Longitudinal Study. Issue 1 (15th November 2015) - Yang, Chunyu; Fu, Hongqiao; Li, Ling
Abstract : Using 2011 China Health and Retirement Longitudinal Study baseline data, this paper examines the effects of family structure on labor force participation. In consideration of the possible endogeneity provoked by family structure, we constructed regression models with instrument variables. Intergenerational co‐residence significantly decreases women's labor force participation by 14%, while it has no effect on men's labor supply. One potential reason for this result is residential circumstance. As it is custom to live with elderly parents in multi‐generation families in China, adult women often share the burden of all housework and are responsible for elderly care; thus, cohabiting with parents seems to have negative effects on female labor participation. On the contrary, Chinese culture dictates that men do not spend as much time as women on housework, thus, the probability of working in the labor market is not influenced by residential circumstance. If women were freed from housework responsibilities, the implication is that their participation in the labor force would increase.